Cooperation, Punishment and Organized Crime: A Lab-in-the-Field Experiment in Southern Italy - Annamaria Nese; Niall O'Higgins; Patrizia Sbriglia; Maurizio Scudiero (Institute for the Study of Labor (IZA), 2016)
This paper reports the results of an experimental investigation which allows a deeper insight into the nature of social preferences amongst organized criminals and how these differ from "ordinary" criminals on the one hand and from the non-criminal population in the same geographical area on the other. We provide experimental evidence on cooperation and response to sanctions by running Prisoner's Dilemma and Third Party Punishment games on three different pools of subjects; students, 'Ordinary Criminals' and Camorristi (Neapolitan 'Mafiosi'). The latter two groups being recruited from within prisons. We are thus able to separately identify 'Prison' and 'Camorra' effects. Camorra prisoners show a high degree of cooperativeness and a strong tendency to punish, as well as a clear rejection of the imposition of external rules even at significant cost to themselves. In contrast, ordinary criminals behave in a much more opportunistic fashion, displaying lower levels of cooperation and, in the game with Third Party punishment, punishing less as well as tending to punish cooperation (almost as much) as defection. Our econometric analyses further enriches the analysis demonstrating inter alia that individuals' locus of control and reciprocity are associated with quite different and opposing behaviours amongst different participant types; a strong sense of self-determination and reciprocity both imply a higher propensity to cooperate and to punish for both students and Camorra inmates, but quite the opposite for ordinary criminals, further reinforcing the contrast between the behaviour of ordinary criminals and the strong internal mores of Camorra clans.
Keywords: A13; D63; D23; C92; K42; Z13; 330; experimental economics; economics of crime; models of identity; prisoner's dilemma; third party punishment